Geographical Information System for the Layout of the Simalungun Protestant Christian Church (GKPS) in Medan City - Simanihuruk, Rohdin Martuah (Jurnal Mekintek : Jurnal Mekanikal, Energi, Industri, Dan Teknologi, 2023)
Geographic Information System is an information system that is used to enter, process, and produce geographically or geospatially referenced data, to support decision making in a plan. In this final project, the author creates a Geographic Information System (GIS) for the layout of the Simalungun Christian Protestant Church (GKPS) in Medan City. This information system will later have a visualization in the form of a web that is used to map the GKPS for the Medan city area. Basically, GKPS is the Church of the Simalungun tribe, most of the services use the Simalungun language. In developing a Geographic Information system for the layout of the Simalungun Protestant Christian Church in Medan City using the PHP programming language, as a method for obtaining recommendations, MySQL as the database system